Hand hygiene and hand eczema: A systematic review and meta‐analysis. (2nd May 2022) - Loh, Enver De Wei; Yew, Yik Weng
Abstract: Hand eczema is a common inflammatory condition of the skin that has been linked to hand hygiene. This systematic review and meta‐analysis aims to determine the risks of hand eczema associated with hand hygiene, including frequency of hand washing, wet work and use of alcohol hand rub. A comprehensive search of MEDLINE, EMBASE and Cochrane Library was performed for cohort, case–control or cross‐sectional studies that analysed the association between hand hygiene and risk of hand eczema. Results of individual studies were presented in respective forest plots and pooled summary relative risks were estimated using a random‐effects model. Forty‐five studies were included in the analysis. Hand washing at least 8–10 times daily significantly increased risk of hand eczema (relative risk [RR] 1.51; 95% confidence interval [CI]: 1.35–1.68; p < 0.001). The risk was related to hand washing frequency, with higher pooled RR of 1.66 (95% CI: 1.51–1.83; p < 0.001) with increased hand washing at least 15–20 times daily. However, use of alcohol‐based hand sanitizer was not significantly associated with risk of hand eczema. Given the widespread implementation of hand hygiene practices during the COVID‐19 pandemic, there is a pertinent need to understand skin care habits specific to the hands to avoid a greater incidence of hand eczema.